Insulin and the sebaceous gland function - Okoro, Obumneme Emeka; Camera, Emanuela; Flori, Enrica; Ottaviani, Monica (Frontiers in Physiology, 2023)
Insulin affects metabolic processes in different organs, including the skin. The sebaceous gland (SG) is an important appendage in the skin, which responds to insulin-mediated signals, either directly or through the insulin growth factor 1 (IGF-1) axis. Insulin cues are differently translated into the activation of metabolic processes depending on several factors, including glucose levels, receptor sensitivity, and sebocyte differentiation. The effects of diet on both the physiological function and pathological conditions of the SG have been linked to pathways activated by insulin and IGF-1.Experimental evidence and theoretical speculations support the association of insulin resistance with acne vulgaris, which is a major disorder of the SG. In this review, we examined the effects of insulin on the SG function and their implications in the pathogenesis of acne.